2021
DOI: 10.3389/fncir.2021.747472
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns of the Neuropeptide Urocortin 3 and Its Receptor CRFR2 in the Mouse Central Auditory System

Abstract: Sensory systems have to be malleable to context-dependent modulations occurring over different time scales, in order to serve their evolutionary function of informing about the external world while also eliciting survival-promoting behaviors. Stress is a major context-dependent signal that can have fast and delayed effects on sensory systems, especially on the auditory system. Urocortin 3 (UCN3) is a member of the corticotropin-releasing factor family. As a neuropeptide, UCN3 regulates synaptic activity much f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 149 publications
0
2
0
Order By: Relevance
“…An alternative mechanism is local stress peptide signalling. Pagella et al (2021) showed that small cells express CRFR2, a urocortin 3 (UCN3) receptor, which can be produced by bushy and stellate cells. However, the contribution of this peptide on small cell activity or auditory signal processing is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative mechanism is local stress peptide signalling. Pagella et al (2021) showed that small cells express CRFR2, a urocortin 3 (UCN3) receptor, which can be produced by bushy and stellate cells. However, the contribution of this peptide on small cell activity or auditory signal processing is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A similar mechanism is adopted by the mammalian system; the distinct topological expression of urocortin 3 (UCN3) and its receptor corticotropin-releasing hormone receptor 2 (CRFR2) are critical for protecting auditory function under stress conditions [ 142 ]. A strong presence of CRFR2 within the subcortical auditory areas [ 143 ] reveals a potential mechanism for sensory cortex activation and auditory signal integration. This involves the activity-dependent release of neuropeptide signals and volume transmission towards neurons expressing the corresponding receptor, not necessarily situated near the source of the stimulus, involved in sensory processing and integration.…”
Section: Function Of Neuropeptides In the Neurological Systemmentioning
confidence: 99%